Reinterpretasi Relasi Suami Istri dalam Membangun Keharmonisan Rumah Tangga (Sebuah Pendekatan Kontekstual terhadap QS. an-Nisaa' (4): 34) - Putri, Dewi; Warman, Arifki Budia; Nabilah, Wardatun; Putri, Siska Elasta; Nofrianti, Mami (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This paper will answer the interpretation of QS. an-Nisaa'(4) : 34 with the method offered by Abdullah Saeed, namely contextual interpretation. This study will answer the research questions, first: how the socio-historical context of the verse was revealed and how the reinterpretation of the verse of husband and wife relations above in the modern context. Using qualitative research methods and collecting data from the literature, the study shows that there are four steps Saeed applies in determining contextual interpretation. The first step is encountering the world of the text in general. Second, critical analysis, which is by understanding the text linguistically, literary context, literary form, related texts, and identification of verses that have similar content and meaning. Third, linking the text with the socio-historical context of the time of revelation to find out how the text was understood by the first recipient. Fourth, connecting the text with the present context. The contextual approach to QS. an-Nisaa' (4): 34, which is adapted to current conditions, is expected to reduce the problem of domestic violence triggered by a sense of superiority and lack of understanding of roles in the family.